Polaris: History of Pulsation Activity since Discovery - Usenko, I.O.; Kovtyukh, V.V.; Miroshnichenko, A.S.; Danford, S. (Science and Innovation, 2024)
The pulsation activity of small-amplitude Cepheid Alpha UMi (Polaris) during the period of its radial velocity observations has been analyzed. In the 20th century, Polaris was known to demonstrate a decrease in radial velocity amplitude to the minimum, in the 1980s. Thereafter, the amplitude has increased. The observations of September-December 2015 (21 spectra) obtained by 81cm telescope TCO with spectrograph have showed that radial velocity amplitude comes to 4.16 km/s and is approximately twice higher than the estimates made in 2007, with pulsation period adding 8.6 min.